Growth variation of Paulownia Sieb. and Zucc. species and origins at the nursery stage in Kastamonu-Turkey - Ayan, Sezgin; Sıvacıoğlu, Ahmet; Bilir, Nebi (Journal of Environmental Biology July 2006, 27(3) 499-504 (2006), 2006)
The present study was carried out on Paulownia tomentosa (6), Paulownia elongate (4), Paulownia fortunei (5) and Paulownia fortunei x tomentosa (1) origins at Kastamonu Forest Nursery. The seedling height growth (SH), root collar diameter (RCD), dry root percentage (DRP) and seedling percentage (SP) of one-year old seedlings of the origins were studied for comparing growth performance of the species and origins and discussing for guidance to field stage based on nursery stage. As a result, P. tomentosa x fortunei hybrid has the highest SH (72.62 cm) among the used species. Significant difference was determined among the origins as to the SH and DRP .The maximum SH were determined for P. tomentosa Beijing-Daxin (81.32 cm) and P. elongata Beijing-Daxin (80.76 cm) origins. The maximum DRP were determined for P. tomentosa Anhui-Tongling (77 %) origin. There were no significant differences based on RCD and SP among the species and the origins. Among the parents, there were important diversities for SH and RCD. As a final remark, observations and evaluations of the Paulownia studies should be included with the clonal variation for further studies because of the observed growth variations within the population.
Keywords: Paulownia, Origin, Adaptation, Nursery stage, Kastamonu.